Super-resolution photoacoustic microscopy using a localized near-field of a plasmonic nanoaperture : a three-dimensional simulation study - Park, Byullee (2018)
Super-resolution microscopy has been increasingly important to delineate nanoscale biological structures or nanoparticles. With these increasing demands, several imaging modalities, including super-resolution fluorescence microscope (SRFM) and electron microscope (EM), have been developed and commercialized. These modalities achieve nanoscale resolution, however, SRFM cannot image without fluorescence, and sample preparation of EM is not suitable for biological specimens. To overcome those disadvantages, we have numerically studied the possibility of superresolution photoacoustic microscopy (SR-PAM) based on near-field localization of light. Photoacoustic (PA) signal is generally acquired based on optical absorption contrast; thus it requires no agents or pre-processing for the samples. The lateral resolution of the conventional photoacoustic microscopy is limited to ~200 nm by diffraction limit, therefore reducing the lateral resolution is a major research impetus. Our approach to breaking resolution limit is to use laser pulses of extremely small spot size as a light source. In this research, we simulated the PA signal by constructing the three dimensional SR-PAM system environment using the k-Wave toolbox. As the light source, we simulated ultrashort light pulses using geometrical nanoaperture with near-field localization of surface plasmons. Through the PA simulation, we have successfully distinguish cuboids spaced 3 nm apart. In the near future, we will develop the SR-PAM and it will contribute to biomedical and material sciences.